Audio–Visual Modeling and its Effect on Behavior of Pediatric Patient: An Observational Study - Sujata Kumari; Amreen Aijazuddin; Anand Nanasaheb Patil; Amish Diwanji; Ranadheer Eeraveni; Disha Makwani; Akshaya Ojha (Journal of Pharmacy and Bioallied Sciences)
Background: The prognosis and patients’ cooperation are interdependent on each other. In case of children, this aspect becomes all the more highlighted because of heightened response to pain and anxiety. Material and Methodology: Hundred (4-to-10 years old) children who were rated as negative on Frankl Behavior Rating Scale were taken for the study. The children were shown a video of a positive child model, and also various procedures of the dental treatment were shown. Results: Sixty-one children out of 100 demonstrated positive behavior and 3 showed definitely positive behavior during preventive treatment procedures. On the other hand, 73 children out of 100 demonstrated positive behavior and 3 showed definitely positive behavior during main treatment procedures. Significant change was observed in behavior of children in before and after the video was shown to them (<0.001). Conclusion: Audio–visual modeling has been proved to be a very efficient method in developing positive behavior of children toward dental treatment.